1998
DOI: 10.1016/s0169-5150(97)00050-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and technical progress in traditional and modern agriculture: evidence from rice production in China

Abstract: Acceptcd 1R Octobcr 1997Ahstract Productive efficicncy for Chincse hybrid and conventional riec production is estirnatcd using a dual stochastic frontier cfficicncy decomposition model, Results reveal significant differences in tcchnical and allocative efficicncy between eonvcntional and hybrid riec production. and indicate significant regional efficiency differences in hybrid riec production. but not in conventional rice production. © 1998Keywords. Hybrid riec production; Conventional riec production: Stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Kalijaran (1991), Xu and Jeffrey (1998), Seidu (2008), Saigenji andZeller (2009), andNyagaka et al (2010) also found that agricultural extension services could help improving technical efficiency. Agricultural extension policy was designed in Vietnam to develop agriculure production in a sustainable way.…”
Section: Factors Affecting Resource Use Efficiencymentioning
confidence: 99%
“…Kalijaran (1991), Xu and Jeffrey (1998), Seidu (2008), Saigenji andZeller (2009), andNyagaka et al (2010) also found that agricultural extension services could help improving technical efficiency. Agricultural extension policy was designed in Vietnam to develop agriculure production in a sustainable way.…”
Section: Factors Affecting Resource Use Efficiencymentioning
confidence: 99%
“…Important among these innovations to intensify traditional agricultural systems are ecological agricultural techniques involving more input of skills, knowledge and labor (Ellis and Wang, 1997;Xu, 2004;Shi, 2002;Battershill and Gilg, 1998), integrated farming systems (Li and Min, 1999), improved germplasm/transgenic plants grown with efficient systems (Xu and Jeffrey, 1995;Soleri et al, 2005) and diversification of farming systems (Short, 1997). Yet, repeated attempts at adoption of improved technologies have been met with modest success in SSA, where food insecurity remains a major issue.…”
Section: Constraints To Transforming Traditional Agriculture In Sub-smentioning
confidence: 99%
“…This is a system of minimum cost input demand equations (Bravo -Ureta and Evenson, 1994;Xu andJeffrey, 1995 andPinheiro, 1997). Substituting a farm's input prices and quantity of output in equation (2) yields the economically efficient input vector X c.. With observed levels of output given, the corresponding technically and economically efficient costs of production will be equal to X ii P and X ie , respectively.…”
Section: Introductionmentioning
confidence: 99%